2022
DOI: 10.3390/antiox11091840
|View full text |Cite
|
Sign up to set email alerts
|

Carob (Ceratonia siliqua) as Functional Feed Is Beneficial in Yellow Mealworm (Tenebrio molitor) Rearing: Evidence from Growth, Antioxidant Status and Cellular Responses

Abstract: In terms of sustainability and circular economy, agricultural by-products may be efficiently reused in insects’ rearing for high-quality protein sources in human diet and animal feeds. The present study aimed to explore whether the utilization of carob pods as feeding substrate may beneficially affect Tenebrio molitor’s growth, nutritional value, antioxidant status and cellular responses. Increasing levels of milled whole carob pods (0, 25, 50, 75, 100%) were used as alternative wheat bran (control) substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…A previous study has reported that many dietary plant-derived polyphenolic components are more effective antioxidants in vitro than vitamins E or C [ 60 ]. The amount of total polyphenols (TPC) in the control sample was found similar to two previous studies by Antonopoulou et al and Keil et al [ 61 , 62 ].…”
Section: Resultssupporting
confidence: 89%
“…A previous study has reported that many dietary plant-derived polyphenolic components are more effective antioxidants in vitro than vitamins E or C [ 60 ]. The amount of total polyphenols (TPC) in the control sample was found similar to two previous studies by Antonopoulou et al and Keil et al [ 61 , 62 ].…”
Section: Resultssupporting
confidence: 89%
“…The larval development of insects is influenced by various factors, including the quality and composition of their diet (Rumbos et al 2021b ; Rumbos and Athanassiou 2021b ; Gourgouta et al 2022 ; Rumbos et al 2022 ; Kotsou et al 2021 ). The enrichment of diets with functional ingredients is a promising approach for enhancing the nutritional quality of insect diets, which can have implications for their growth and development but also affects their nutritional profile (Andreadis et al 2021 ; Antonopoulou et al 2022 ). Our findings indicate that the enrichment with the ingredients of both mixtures can positively affect larval development, as demonstrated by the survival, final larval weight, and development time of the larvae reared on the enriched diets.…”
Section: Discussionmentioning
confidence: 99%
“…Insects have been presently recognized not only as a source of nutrition but also as a dietary component that possesses a broad range of activities against pathogens, attributed to their ability to produce antimicrobial peptides (AMPs). In addition, given that the nutrient composition of insects is influenced by their diet, it is possible that the nutritional value of insects could be transferred to animals when used as a feed source (Andreadis et al 2021 ; Rumbos et al 2022 ; Antonopoulou et al 2022 ). Furthermore, it appears that the majority of the population is comfortable with consuming meat products derived from livestock that were fed with insect-based feed (Verbeke et al 2015 ; Mancuso et al 2016 ; Sebatta et al 2018 ; Popoff et al 2017 ; Ferrer Llagostera et al 2019 ; Kulma et al 2020 ; Rumbos et al 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…The industrial applications of carob seeds were reviewed by Barak and Mudgil (2014), while carob flour is increasingly used in bakeries (Correia, Pestana 2018;Papaefstathiou et al, 2018;Papageorgiou et al, 2020) with potential benefits for human health and the environment, as it can be obtained with a reduced environmental impact. In addition, carob pods and their antioxidant properties exert beneficial effects on the rearing and nutritional status of Tenebrio molitor, an insect with high-quality protein, used as a source in the human diet and in animal feeds (Antonopoulou et al, 2022).…”
Section: Economic Importancementioning
confidence: 99%